PERAN GURU HINDU DALAM BIMBINGAN MORAL DAN ETIKA SISWA HINDU MELALUI KEGIATAN SRADHA DAN BHAKTI - Sintia, Ni Kadek; Wiguna, Ida Bagus Alit Arta; Santika, Dewa Made Rama; Leslesy, Wiwin; Sutariani, Ni Nyoman (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
This study aims to analyze the implementation of moral and ethical guidance at SMA Negeri 3 Mataram through sradha and Bhakti activities. Moral and ethics are important in the world of education because at this time students are very vulnerable to moral and ethical degradation. This guidance is an effort by teachers to help individuals understand and apply moral and ethical principles in everyday life. This research is a qualitative approach that uses data collection methods in the form of non-participant direct observation, structured direct interviews and documentation. In this study, data analysis was carried out by data reduction, data presentation, and conclusion. based on the results of data analysis, it is concluded that teachers have an important role in moral and ethical guidance at SMA Negeri 3 Mataram. teachers are not just supervisors who oversee the activities but more than that teachers have a role as role models, motivators, support systems, and enforcers of justice. Although the implementation of guidance does not experience significant obstacles, the obstacles that are often experienced by teachers are students who arrive late and students who are stubborn and difficult to communicate personally.